Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages scurvy, and lime juice was given to them because, as we now know, it contains Vitamin C, without which scurvy develops. It ought not to be necessary to add these vitamins, for a varied and satisfactory diet contains sufficient of them in a natural form. The addition of them to a diet is a confession that the diet is unsatisfactory. There are, of course, other factors besides food which exert an influence on health. Bad housing is, per se, harmful, but good housing alone cannot compensate for the evil effects of a bad diet. This was well illustrated in the Stockton-on-Tees investigation which showed that the death rates of a slum population which had been rehoused in a new municipal housing estate were, over a period of years, actually worse than they had been in the slum. The reason for this unexpected state of affairs was found to be that the increased rents of the new houses diminished the food-purchasing power of the tenants who were nearly all unemployed. The quantities of protective foods bought by the tenants of the new houses were less than among other families who remained in a nearby slum. Investigations made by Sir John Orr have shown clearly that as income falls the quantities of the protective foods purchased fall, and that there are four million people in this country who are unable to spend more than four shillings per head per week on food. (See Food, Health and Income, by JOHN BOYD ORR, Macmillan & Co.). It is not possible to purchase a diet which will maintain health on this amount. Further, there are more millions who can purchase slightly more than this but who are unable to attain the British Medical Association's minimum diet. Other investigations confirm this, and in Stockton-on-Tees it has been 8 15X/2/217/2